Alvin and the Chipmunks. Chipwrecked [videorecording (DVD)] - Mitchell, Mike (Director); Poehler, Amy, 1971-; Lee, Jason, 1970-; Long, Justin, 1978-; Applegate, Christina, 1971-; Cross, David, 1964-; Gubler, Matthew Gray, 1980-; Faris, Anna, 1976- (20th Century Fox Home Entertainment, 2012)
The vacationing Chipmunks and Chipettes are turning a luxury cruise liner into their personal playground, until they become 'chipwrecked' on a remote island. As the 'Munks and Chipettes try various schemes to find their way home, they accidentally discover their new turf is not as deserted as it seems.